Entrepreneurial migration in an integrated world - Bougheas, Spiros; Falvey, Rod (Wiley, 2017)
A growing number of developed countries are offering entrepreneurial visas as a means of attracting entrepreneurial talent and capital. In this paper we use a simple two sector model of international trade with heterogeneous agents and financial frictions to show that entrepreneurial migration can contribute to the international efficiency of production, even when capital also flows internationally through borrowing and lending and foreign direct investment. In our model all cross-border transactions are motivated by cross-country variations in the quality of financial institutions.